Pengaruh Loyalitas Pelanggan Terhadap Kualitas Layanan, Kepuasan dan Kepercayaan Pada E-Commerce Shopee - Esa Miftakhul Ullumia; Angga Sanita Putra (Peneliti.net, 2023)
In the current digital economy era, technology is used by the business world as a marketing tool and product sales aimed at improving the economy. So that many business actors use the internet to enliven the development of e-commerce such as Shopee so that they can meet people's needs. This study aims to observe the views of Shopee users on several factors, namely service quality, satisfaction, and trust in order to create loyalty to the Shopee marketplace. In addition to that, you can see how much these factors influence partially and simultaneously. The method used in research is an associative method using quantitative research. The sample in this research was taken by applying the non-probability sampling method and the non-probability sampling method used was judgmental sampling, which consisted of 100 respondents. The methods applied in analyzing the data are validity and reliability tests, classic assumption tests, and hypothesis testing. Based on the results of the t-test, it was found that a significant influence on service quality, satisfaction, and trust was affected by the loyalty variable, but satisfaction did not have a significant effect on Shopee e-commerce loyalty. While the f test shows that loyalty simultaneously has a significant effect on service quality, satisfaction, and trust in Shopee e-commerce.